Baseline Severity of Sacroiliitis and Extensive Fat Metaplasia Predicts the Progression of Backfill at the Sacroiliac Joint in Patients With Axial Spondyloarthritis - Zhang, Yimeng; Guo, Zikang; Wang, Lisong; Zhan, Ying; Qu, Jin; Lei, Xinwei (Frontiers in Immunology, 2022)
Objectives: Fat metaplasia in an erosion cavity, also known as backfill, is an essential intermediary in the development of new bone formation with axial spondyloarthritis (axSpA) patients but the predictors of backfill progression are unknown. This longitudinal study aimed to assess the predictors of backfill progression in axSpA patients on MRI. Method: Clinical and MRI data were collected at baseline and follow-up in 52 axSpA patients. The backfill progression was defined as the development of backfill morphologically or scored using the Spondyloarthritis Research Consortium of Canada sacroiliac joint structural scoring (SPARCC-SSS) method. Logistic regression analyses were performed to identify predictors associated with backfill progression. Results: Nineteen (36.5%) patients had ‘backfill’ at baseline. Thirty (57.7%) patients had ‘backfill’ progression after follow-up. The mean disease duration and SPARCC scores at baseline were significantly different between patients with backfill progression and those without (P < 0.001, P = 0.003, respectively). Patients with backfill progression had a higher frequency of backfill at baseline and higher SSS scores of fat metaplasia and backfill than those without (P = 0.001, P < 0.001, and P = 0.002, respectively). Higher FF value in the fat metaplasia area at baseline was more frequent in patients with backfill progression (P = 0.019). In the univariate logistic regression analyses, a higher SPARCC score of inflammation and a higher SSS score of fat metaplasia at baseline were associated with new backfill. Conclusions: Severity of sacroiliitis and extensive fat metaplasia at baseline are predictors of the backfill progression in axSpA patients.